2016
DOI: 10.1002/pssb.201600233
|View full text |Cite
|
Sign up to set email alerts
|

Stress and charge transfer in uniaxially strained CVD graphene

Abstract: Mechanical properties of graphene prepared by chemical vapor deposition (CVD) are not easily comparable to the properties of nearly perfect graphene prepared by mechanical cleavage. In this work, we attempt to investigate the mechanical performance of CVD graphene (simply supported or embedded in polymer matrix), transferred by two different techniques, under uniaxial loading with simultaneous in-situ monitoring by Raman microspectroscopy. The level of charge transfer doping and strain is assessed using the v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…PMMA as well as on SU-8. 13 On the other hand, in the present case, the graphene conforms well on the substrate without the presence of delaminated areas. This can be deduced by the fact that the polymer is also wrinkled along with the graphene as a unified system (figure 1).…”
Section: Mechanical Response Of Wrinkled As Compared To 'Flat' Graphementioning
confidence: 47%
See 1 more Smart Citation
“…PMMA as well as on SU-8. 13 On the other hand, in the present case, the graphene conforms well on the substrate without the presence of delaminated areas. This can be deduced by the fact that the polymer is also wrinkled along with the graphene as a unified system (figure 1).…”
Section: Mechanical Response Of Wrinkled As Compared To 'Flat' Graphementioning
confidence: 47%
“…15 Even though the dimensions of those islands can be modified to some extent depending on the transfer method, 13 the delaminated wrinkles which cause a sincere drop in the interfacial stress transfer are present on different kinds of polymers as PET 14 , PMMA as well as on SU-8. 13 On the other hand, in the present case, the graphene conforms well on the substrate without the presence of delaminated areas. This can be deduced by the fact that the polymer is also wrinkled along with the graphene as a unified system (figure 1).…”
Section: Mechanical Response Of Wrinkled As Compared To 'Flat' Graphe...mentioning
confidence: 99%
“…For exfoliated graphene/ PMMA systems the maximum values recorded are in the range of 55-60 cm -1 /% for the 2D peak and ~25cm -1 /% for the mean value of the G peak [99]. For corresponding CVD graphene/ PMMA systems the above values represent upper limits often difficult to attain due to the inherent morphological defects of the CVD-grown graphene [19,34,100]. In this context, strain rate maps extracted for both loading and unloading cycles can actually be considered as an indirect adhesion indicators, since the measured Raman variations shifts of Pos(2D) and Pos(G) are related with the "true" strain transferred from the matrix to the inclusion.…”
Section: Implementation Of Mechanical Loadingmentioning
confidence: 99%
“…Electron/hole doping or n -type/ p -type doping in graphene introduced a red/blueshift in the Raman spectrum, and the magnitude of the shift and relative 2D band intensity with respect to undoped graphene depended on the dopant concentration [ 56 ]. Graphene subjected to tensile/compressive strain also strongly affected the red/blueshift of the Raman spectrum owing to the elongation of the C–C bond [ 2 , 10 , 57 ]. The redshift Raman spectrum in the ITO nanoparticle-decorated graphene revealed that the ITO nanoparticles introduced an n-type doping effect with lattice distortion on the graphene.…”
Section: Resultsmentioning
confidence: 99%